Psychological Interventions For Diabetes Patients During The COVID-19 Pandemic - Ratna Wulandari; Heni Dwi Windarwati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
COVID-19 can trigger increased stress in diabetes people because they are vulnerable to experiencing psychological disorders. The stress experienced by people with diabetes can lead to hyperglycemia which is one of the causes of the poor prognosis of people with diabetes infected with COVID-19. This article aims to develop guidelines for psychological interventions in people with diabetes during the COVID-19 pandemic. We analyzed scientific articles on four databases, namely PubMed, ProQuest, EBSCO, and ScienceDirect. The quality of the articles was assessed using PRISMA based on predefined inclusion and exclusion criteria. The results of the literature review were 1041. Then, 61 articles were reviewed in full text. A total of 24 literatures that met the inclusion and exclusion criteria were analyzed in this article. There are three psychological intervention guidelines for people with diabetes during a pandemic, namely the psychological response of people with diabetes during the pandemic, psychological intervention for people with diabetes during the pandemic, and psychological intervention methods for people with diabetes during the pandemic. People with diabetes are a vulnerable group during the COVID-19 pandemic, so guidelines for psychological intervention in people with diabetes are essential to support and improve the mental health of people with diabetes during the pandemic. Abstrak: Penderita diabetes merupakan kelompok rentan untuk mengalami permasalahan psikologis selama masa pandemi Coronavirus disease atau COVID-19. Artikel ini bertujuan untuk menyusun pedoman intervensi psikologis pada penderita diabetes selama masa pandemi COVID-19. Penulis melakukan analisis terhadap pedoman intervensi psikologis diabetes pada masa pandemi dari dua Negara. Penulis kemudian melakukan analisis artikel ilmiah pada empat database yaitu Pubmed, Proquest, EBSCO dan ScienceDirect. Kualitas artikel dinilai menggunakan PRISMA berdasarkan kriteria inklusi dan eksklusi yang telah ditetapkan. Terdapat 2 panduan dari 2 Negara. Hasil pencarian literatur adalah sebesar 1041. Kemudian 63 artikel ditinjau secara fulltext. Sebanyak 26 literatur yang memenuhi kriteria inklusi dan ekslusi dianalisis dalam artikel ini. Terdapat 3 panduan intervensi psikologis pada penderita diabetes pada masa pandemi yaitu respon psikologis penderita diabetes pada masa pandemi, intervensi psikologis penderita diabetes pada masa pandemi dan metode intervensi psikologis penderita diabetes selama masa pandemi. Penderita diabetes merupakan kelompok rentan selama masa pandemi COVID-19, sehingga pedoman intervensi psikologis pada penderita diabetes merupakan hal yang penting untuk mendukung dan meningkatkan kesehatan mental penderita diabetes selama masa pandemi.